Fresno County Bar Association Luncheon With Keynote Speaker Fresno Mayor Dan Whitehurst - Watkins, Howard::::::::: (1982)
State Bar Pro Bono Representative Peggy Walsh reading Recognition Award to Robert Oliver as President of Fresno County Bar Association; Dan Whitehurst and Doug Jensen at head table